Effects of two types of restraint stress on spontaneous behavior of Sprague-Dawley and Lewis rats - Klenerová, V; Sída, P; Krejcí, I; Hlinák, Z; Hynie, S (Journal of physiology and pharmacology, 2007)
The purpose of this study was to evaluate the action of two types of stressors in Sprague-Dawley (S-D) and Lewis (LEW) rats differing in their hypothalamic-pituitary-adrenal axis activity on locomotion and rearing in an open space. Exposure to restraint immobilization alone (IMO) or this immobilization combined with cold water (22 degrees C) immersion (IMO+C) lasted for 1 h and started 2 or 5 h before the test. To evaluate the acute and persisting effects of both stressors, four trials were performed in one-week intervals; rats were exposed to the stressors in trial 1 and 3. While in LEW rats both acute stressors produced reduction of locomotion and rearing in all stressed groups, S-D rats responded with a decrease of both parameters only after IMO+C presented 2 h before testing. Neither strain displayed a changed performance one week after the first stress exposure. One week after the second stress exposure rats of both strains exhibited a tendency to an increase of both parameters reaching the significance in several experimental groups. The findings indicate: a) the IMO+C produced stronger behavioral alteration than IMO alone; b) the behavioral responses to stressors were more pronounced in LEW compared to S-D strain; c) change from the reduction of activity to its increase may be interpreted as bi-directional manifestation of long-term effects of immobilization stress.
Keywords: psychický stres; Exploratory Behavior; fyzické omezení; krysa rodu Rattus; potkani Sprague-Dawley; Rats, Inbred Lew; chování zvířat; pátrací chování; Cold Temperature; Species Specificity; druhová specificita; Rats, Sprague-Dawley; mužské pohlaví; lokomoce; zvířata; potkani inbrední LEW; Restraint, Physical; Time Factors; Rats; Stress, Psychological; Animals; časové faktory; Male; Locomotion; nízká teplota; Behavior, Animal